Boston journal of natural history - Boston Society of Natural History ([Boston Society of Natural History], 1837)
"Containing papers and communications read to the Boston Society of Natural History."
Keywords: Natural history : Periodicals : Congresses; Natural History : Periodicals; Natural History : Societies, etc; Natural history